2019
DOI: 10.1016/j.mjafi.2018.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Scrub typhus strikes back: Are we ready?

Abstract: Scrub typhus has struck back, albeit with renewed vigour, impacting areas with previously known endemicity as also impressing newer expanses. It is not surprising, therefore, that Scrub typhus has emerged as a leading cause of public health concern globally as well as in India, but are we ready to take on the challenge? Over the last decade, there has been a global increase in the number of outbreaks of Scrub typhus, be it the military occupied areas or the civil population at large. The innumerable outbreaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 44 publications
(46 reference statements)
1
27
0
Order By: Relevance
“…At present, while its endemic areas continue to broaden in Asian regions, strong molecular, serological and clinical evidence suggested that this disease has spread in Africa and South America (Diaz et al, 2018 ). And the incidence of this disease is increasing worldwide (Yang and Zhao, 2008 ; Tilak and Kunte, 2019 ). Currently, cases of vertical transmission through the mother to the baby have been observed (Suntharasaj et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, while its endemic areas continue to broaden in Asian regions, strong molecular, serological and clinical evidence suggested that this disease has spread in Africa and South America (Diaz et al, 2018 ). And the incidence of this disease is increasing worldwide (Yang and Zhao, 2008 ; Tilak and Kunte, 2019 ). Currently, cases of vertical transmission through the mother to the baby have been observed (Suntharasaj et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than 40 serotypes or antigenic strains of O. tsutsugamushi been isolated worldwide (Tilak and Kunte, 2019 ). The most common genotype is Karp, following by Gilliam (Kelly et al, 2009 ; Tilak and Kunte, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scrub typhus, also known as tsutsugamushi disease, is a bacterial infection transmitted by larval trombiculid mites from rodents often during cooler months. The causative organism is Orientia tsutsugamushi , an obligatory intracellular bacterium that leads to the formation of eschar at the inoculation site followed by fever, headache, myalgia, generalized lymphadenopathy, cough, gastrointestinal symptoms, transient hearing loss, and rash [1]. Further progression of the disease may manifest as acute respiratory distress syndrome, meningoencephalitis, gastrointestinal bleeding, acute renal failure, and coagulopathy [2].…”
Section: Introductionmentioning
confidence: 99%
“…Look out for a reality check on scrub typhus as an emerging threat in this issue! 7 Entering 75 years of regular publishing, MJAFI will celebrate 2019 as a Platinum jubilee year. This will be an occasion to reflect, remodel and rededicate us to the challenges ahead.…”
mentioning
confidence: 99%